Cyprus: The EU’s Role in Europe’s Last Divided Country - Zupančič, Rok; Kocan, Faris; Andresen, Kenneth; Bojarska, Katarzyna; Dacosta, Ricardo; Farrell, Seamus; Fiedler, Anke; Hoxha, Abit; Ioannidis, Nikandros; Niamh, Kirk; Irene, Martín; Milioni, Dimitra L.; et al. (My University, 2023)
This chapter begins with a description of the relationship between two communities in Cyprus, Greek Cypriots and Turkish Cypriots, and their struggles in their long bi-communal conflict. After the explanation of the methodological approach, the chapter continues with the review of the European Union (EU)’s historical connection to the Cyprus Problem. It divides the role of the EU in three time periods mainly based on the magnitude of the EU’s involvement: the EU pre-accession period (roughly from 1973 to 1997); the EU accession talks period until the 2004 Annan plan referendum (from 1998 to 2004); and the post-accession period (from 2004 onwards). The chapter also gives a non-exclusive list of policy recommendations for each of the four topical areas and concludes by summarizing the implications as well as the limitations of the present study juxtaposed with opinions expressed in interviews with selected policy makers and stakeholders.
Keywords: Annan plan referendum; bi-communal conflict; Cyprus; Greek Cypriots; policy recommendation; Turkish Cypriots